Sex Chromosome Inactivation in the Male - Yan, Wei (2009)
Mammalian females have two X chromosomes, while males have only one X plus a Y chromosome. In order to balance X-linked gene dosage between the sexes, one X chromosome undergoes inactivation during development of female embryos. This process has been termed X-chromosome inactivation (XCI). Inactivation of the single X chromosome also occurs in the male, but is transient and is confined to the late stages of first meiotic prophase during spermatogenesis. This phenomenon has been termed meiotic sex chromosome inactivation (MSCI). A substantial portion (~15–25%) of X-linked mRNA-encoding genes escapes XCI in female somatic cells. While no mRNA genes are known to escape MSCI in males, ~80% of X-linked miRNA genes have been shown to escape this process. Recent results have led to the proposal that the RNA interference mechanism may be involved in regulating XCI in female cells. We suggest that some MSCI-escaping miRNAs may play a similar role in regulating MSCI in male germ cells.